Which conditions facilitate the effectiveness of large-group learning activities? A systematic review of research in higher education. (3rd July 2021) - Jerez, Oscar; Orsini, Cesar; Ortiz, Catalina; Hasbun, Beatriz
ABSTRACT: Large-group activities have increased in higher education since 2000. Research focused on the possibility to have positive effects on students' learning, regardless of the number of students by identifying facilitating factors. Hence, the achievement of learning results is used as a criterion of effectiveness. This review summarises the findings of research studies on conditions that determine the effectiveness of large-group learning activities in higher education contexts published from 1996 to 2016. The PRISMA declaration for conducting literature reviews was followed. Articles were searched through the ERIC, Web of Science, SCOPUS, SCIELO, and EBSCO databases, including additional sources. A total of 78 articles met the inclusion criteria and were selected for thematic analysis. These studies came from a wide range of disciplines, types of institutions, and locations. Five themes emerged as conditions that facilitate the effectiveness of large-group learning activities: (1) student–teacher and student–student interaction, (2) implementation of active learning strategies, (3) classroom management, (4) students' motivation and commitment, and (5) the use of online teaching resources. The discussion is centred on the conditions by which large-group activities can be effective learning strategies in terms of student's achievement of learning outcomes.